Determination of Maintenance Method for Turbine Pump Engine Based on Markov Analysis - Anthara, I Made Aryantha; Andriani, Diana; Nugraha, M L; Akbar, A (International Journal of Research and Applied Technology (INJURATECH), 2024)
The purpose of this research is to determine the type of maintenance method that can be applied to the C1107 engine in the company. The C1107 engine is a turbine pump machine used in the manufacture of fertilizers. The main problem discussed in this study is the frequency of damage that occurs in the C1107 engine is quite large, and this will impact the maintenance costs incurred by the company. The types of damage that occurred were categorized into four states, namely good condition, minor, moderate, and high damage. The method used in this research is the Markov analysis method, where, in this method, the value of the transition probability to the steady-state condition will be sought from the transition probability of the failure condition of the CII07 engine used by the company. From the results of the research conducted, it was found that the steady-state status was good, the damage was minor, moderate, and severe, respectively by 11.50, 61.40, 18.70, and 8.40%. The types of maintenance that can be applied are the type of repair maintenance in severe damage conditions and the type of preventive maintenance in moderate damage conditions with a total cost of Rp. 25,042,826. The benefit obtained in this research is to determine the best type of C1107 engine maintenance for the company.